KUALITAS FRAKSI SERAT PAKAN SILASE DAUN PELEPAH SAWIT DENGAN PENAMBAHAN AMPAS TAHU DAN TEPUNG JAGUNG - Harahap, Anwar Efendi; Mucra, Dewi Ananda; Sepriadi, Sigit; Zumarni, Zumarni; Aulia, Wafa (Unpad Press, 2025)
Palm frond leaves can be used as ruminant feed with the addition of tofu dregs and corn flour in the form of complete silage. The aim of the research is to convey the quality of the fiber fraction of palm frond leaf silage by adding various sources of tofu dregs concentrate and corn flour. This research method used a Completely Randomized Design (CRD) with 4 treatments and 5 arranged replications, namely: P0 = 100% PFL (palm frond leaf); P1 = 100% PFL + 5% molasses; P2= 100% PFL + 5% tofu dregs (TD)+ 5% corn flour (CF) + 5% molasses; P3= 100% DPS + 10% tofu dregs (TD)+ 10% corn flour (CF) + 5% molasses and P4 = 100% DPS + 15% tofu dregs (TD)+ 15% corn flour (CF) + 5%. The parameters measured were NDF, ADF, hemicellulose, lignin and cellulose (%). The research results showed that the treatment with the addition of tofu dregs concentrate and corn flour had a significant effect (P>0.05) on the NDF, ADF, cellulose and lignin content of palm frond silage. The use of silage treatment with a composition of 100% palm frond leaves + 15% tofu dregs + 15% corn flour is the best treatment because it is able to optimally reduce the content of NDF (57.15%), ADF (39.05%) and lignin (9.53%)